THE RELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND THE INCIDENCE OF HYPERTENSION IN THE ELDERLY IN LAMME VILLAGE, JAYA DISTRICT, ACEH JAYA REGENCY - Karma, Taufiq; Yurianda, Zuhra (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2024)
Hypertension is a condition where there is an increase in systolic blood pressure ≥ 130 mmHg and diastolic pressure ≥ 80 mmHg. Hypertension is a worldwide health problem that continues to increase. Physical activity is any body movement produced by skeletal muscles and requires energy expenditure. The purpose of this study was to determine the relationship between physical activity and the degree of hypertension in residents of Lamme village, Jaya sub-district. The research design is using analytical observations, using a Cross Sectional approach. The sample was 44 respondents who were taken with purposive sampling technique. Data was collected from respondents using the NCD questionnaire sheet. The results showed that there was a relationship between history of hypertension, age, and physical activity. However, there is no relationship between gender, indicating that gender has a risk of developing hypertension, it's just that its occurrence depends on age.